The Analysis of Students’ Interest in A State Vocational High School (SMKN) 3 Based on Ethnics in Singkawang - Slamat Fitriyadi; Kamaruddin Kamaruddin; Elenita Natalio Que; Heru Susanto (International Journal of Multi Discipline Science, 2022)
This research aims to find out the students' interest in studying in State Vocational High School 3 of Singkawang based on ethnics that live in Singkawang which area consists of Dayak, Malay, Madura, and Chinese. The qualitative method was used in this research. The subjects of this study were 5 students from each ethnic which the total of them are twenty students who were considered able to represent and provide the data needed by researchers. The object of the study was students' learning interests based on Dayak, Malay, Madura, and Chinese ethnics. In this study, sampling techniques were used purposive sampling techniques. The data analysis in this study used the Miles and Huberman model by collecting data at the time the learning process takes place, and after completion of data collection within a certain period. The results of this study showed that students' learning interests based on ethnics were: (1) students who come from the Dayak ethnic tend to be more enthusiastic and interested in learning if the teachers who teach are from the same ethnic and have a tendency to only be interested in certain lessons in their field; (2) most students from the Malay ethnic have a high interest in learning in all the lessons in their field and a tendency to like teachers who have different ethnics; (3) Madura students have a higher learning interest when they were taught by teachers from the same ethnic and most students only interested in certain lessons, (4) most students from Chinese ethnic do not mind the ethnic background of the teacher who teaches and they have very high enthusiasm and interest in pursuing their field.